Heme redox potentials hold the key to reactivity differences between nitric oxide reductase and heme-copper oxidase - Bhagi-Damodaran, Ambika (Proc Natl Acad Sci U S A, 2018)
Despite high structural homology between NO reductases (NORs) and heme-copper oxidases (HCOs), factors governing their reaction specificity remain to be understood. Using a myoglobin-based model of NOR (Fe(B)Mb) and tuning its heme redox potentials (E°′) to cover the native NOR range, through manipulating hydrogen bonding to the proximal histidine ligand and replacing heme b with monoformyl (MF-) or diformyl (DF-) hemes, we herein demonstrate that the E°′ holds the key to reactivity differences between NOR and HCO. Detailed electrochemical, kinetic, and vibrational spectroscopic studies, in tandem with density functional theory calculations, demonstrate a strong influence of heme E°′ on NO reduction. Decreasing E°′ from +148 to −130 mV significantly impacts electronic properties of the NOR mimics, resulting in 180- and 633-fold enhancements in NO association and heme-nitrosyl decay rates, respectively. Our results indicate that NORs exhibit finely tuned E°′ that maximizes their enzymatic efficiency and helps achieve a balance between opposite factors: fast NO binding and decay of dinitrosyl species facilitated by low E°′ and fast electron transfer facilitated by high E°′. Only when E°′ is optimally tuned in Fe(B)Mb(MF-heme) for NO binding, heme-nitrosyl decay, and electron transfer does the protein achieve multiple (>35) turnovers, previously not achieved by synthetic or enzyme-based NOR models. This also explains a long-standing question in bioenergetics of selective cross-reactivity in HCOs. Only HCOs with heme E°′ in a similar range as NORs (between −59 and 200 mV) exhibit NOR reactivity. Thus, our work demonstrates efficient tuning of E°′ in various metalloproteins for their optimal functionality.